STUDI KEBIJAKAN PERIZINAN KABUPATEN SOLOK DI BIDANG PERTAMBANGAN PASCA REFORMASI - Rinaldi Rosba (JIAGANIS, 2016)
Abstract : The arrangement on the new mining born after 10 (ten) years of reformation, that is on January 12 in 2009 with the enactment of Law No. 4 in 2009 on Mineral and Coal Mining. The birth of this Act brings new hope to the arrange of mineral and coal mining in Indonesia that were previously regulated in Law No. 11 in 1967 on Basic Provisions of Mining. However, behind the expectations turned out such problems arise in the implementation of the Act. In it implementation, it turns out many of the parties are not ready to run the rule, including local governments and employers mines in the area. To overcome this problem, the Government at regency of Solok create a licensing policy in the mining sector in Solok. In order for mining activities in Solok can continue to run. This research is focussed on 2 (two) problems, that is: (1) what kinds licensing policy of the government at regency of Solok in the field of mining at post-reformation? (2) how the influence of the licensing policy of the government at regency of Solok to the mining that exist in Solok? This research use the empiric juridical approach method that is descriptive, that is the legal research connecting between regulations or the applicable legal norms with reality in the field. The main data in this research is primary data that is collected by using the semi–structured interview method. The secondary data as the supportive data is obtained by studying the documents. The results of this research showed: (1) the licensing policy of the government at regency of Solok in the field of mining at post-reformation be seen from 2 (two) things, that is: firstly, the licensing policy of the government at regency of Solok in the field of mining for mining companies, and secondly, the licensing policy of the government at regency of Solok in the field of mining for the mining people; (2) the influence of the licensing policy of the government at regency of Solok to the mining that exist in Solok can not be seen clearly. This is because, the policy will be executed to remember that problems arise with the enactment of legislation that is new.Keywords: policy, licensing, mining